BETWEEN ALLEYS AND HOPE: EXPERIENCING THE RESILIENCE OF SANTA LUZIA - Pazos, Valmor Cerqueira; Buzar, Edeilce Aparecida Santos; Pantoja, João da Costa; Guinancio, Cristiane; Menezes, Erika Stella Silva; Jorge, Marcus Vinicius da Silva; Vilela , Erick Alexandre Silva; de Andrade , Liza Maria Souza (Seven Editora, 2024)
This study explores the community of Santa Luzia, located in Brasilia, Brazil, as an emblematic example of the intersection between socio-environmental challenges and agro-ecological resilience. The community faces inadequate urban infrastructure, with unpaved roads and a lack of basic sanitation, resulting in precarious housing that is vulnerable to environmental adversities. Despite these adverse conditions, the community is remarkable for its ability to adapt and innovate in the face of scarce resources and institutional neglect. The practice of agroecology has emerged as a sustainable solution to combat food insecurity and promote biodiversity, potentially strengthening the community’s autonomy and contributing to ecological balance. The environmental analysis revealed a complex interaction between urban challenges and sustainability, emphasizing the need for more effective urban planning. The study proposes specific interventions, including the development of an agro-ecological corridor to sustainably integrate residential areas with the surrounding environment. This planning aims not only to improve residents’ quality of life, but also to strengthen the community’s environmental resilience, highlighting the fundamental importance of community participation and innovation for a sustainable future. DOI: https://doi.org/10.56238/sevened2024.037-070